2005
DOI: 10.1002/pmic.200401141
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of hepatitis B virus‐associated hepatocellular carcinoma: Identification of potential tumor markers

Abstract: Hepatocellular carcinoma (HCC) is a malignancy of both underdeveloped and developing countries. Proteomes of ten pairs of clinical hepatitis B virus associated HCC tissue samples were obtained by high resolution two-dimensional gel electrophoresis. Comprehensive analyses of proteins associated with B-type HCC were focused on total differentially expressed proteins (> or = two-fold increase or decrease, Student's t-test, p < 0.05) from one pair of samples. Protein identification was done by peptide mass fingerp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
80
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(86 citation statements)
references
References 54 publications
(22 reference statements)
5
80
1
Order By: Relevance
“…(38,(40)(41)(42)(43)(44)(45)(46)(47)(48)(49) However, with the exception of vinculin (14,15) the genes reported to be associated with early recurrence of HCC in transcriptomic studies were not identified in this study, a fact possibly due to the current detection limitations of 2D-DIGE using the CyDye DIGE Fluor minimal dye. To improve the sensitivity of our proteomic studies, we are now considering the use of prefractionation methods, narrow range IPG gels, more sensitive fluorescent dye such as the CyDye DIGE Fluor saturation dye, and larger format 2D gels.…”
Section: Discussioncontrasting
confidence: 51%
“…(38,(40)(41)(42)(43)(44)(45)(46)(47)(48)(49) However, with the exception of vinculin (14,15) the genes reported to be associated with early recurrence of HCC in transcriptomic studies were not identified in this study, a fact possibly due to the current detection limitations of 2D-DIGE using the CyDye DIGE Fluor minimal dye. To improve the sensitivity of our proteomic studies, we are now considering the use of prefractionation methods, narrow range IPG gels, more sensitive fluorescent dye such as the CyDye DIGE Fluor saturation dye, and larger format 2D gels.…”
Section: Discussioncontrasting
confidence: 51%
“…In addition to snoRNAs, the upregulation of R2TP has also been reported in various cancer cells as shown in Table 2. For example, in human hepatocellular carcinoma (HCC), the mRNA and/or protein levels of RuvBL1/ pontin and RuvBL2/reptin are increased as compared to non-tumor liver (55)(56)(57)(58)(59)(60). Also, it has been shown that RuvBL1/pontin is overexpressed in breast, colon, and colorectal cancers (61)(62)(63)(64) and RuvBL2/reptin is overexpressed in breast, colon, gastric, and renal cell cancers (62,(65)(66)(67).…”
Section: Potential Role Of R2tp In Tumorigenesis Through Snornp Pathwaymentioning
confidence: 99%
“…2-DE was performed according to the methods described previously. 7 We repeated each 2-DE experiment four times to confirm the spot patterns before proceeding with further analysis. Matching accuracy was 50%.…”
Section: Two-dimensional Gel Electrophoresis (2-de)mentioning
confidence: 99%